Learning Loss in Online Learning for Writing Class - Yulia Astika; M. Zaim (Journal of English Language Teaching, 2022)
Due to the Covid-19 outbreak, learning had to be changed from face-to-face activities in class distance learning. While distance learning is already supported by a number technologies, there are still gaps that cause learning to be lacking effective. One concern is long-term online learning can lead to learning loss or reduced academic knowledge. This study aims to know the platform used in writing class, the advantages and disadvantages of online learning, and learning loss that happened in writing class. The participant of this study were students of the 2021 English Language Education study program who learned paragraph writing, totaling 23 students filled out questionnaires. This study used  descriptive method with a qualitative approach. The researcher used purposive sampling technique. In collecting data, the researcher used questionnaires. The results of the study show that: (1) applications that are often used in online learning are LMS/E-Learning and WhatsApp, (2) advantages of online learning, Online learning can reduce operational lecture costs such as transportation to campus (gas money), (3) disadvantages of online learning, online learning is limited due to students’ domicile and poor internet network access, (4) learning loss in online learning, including: students struggle to study for complex material while studying online, students cannot ask their friends to correct grammatical errors, and students have trouble finding examples of natural English writing.